Multicriteria analysis model in the evaluation of different crops for biodiesel production - Guardiola, Juan Fernando Herrera; Lopes, Rafaela Ferreira; Mello, João Carlos Correa Baptista Soares de; Silva, Flávio Castro da (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2018)
Macbeth model is a multicriteria tool for the multicriteria decision making that has been used in different projects and studies of renewable energies. The purpose of this paper was apply the software Macbeth for the evaluation of canola, corn, palm and soy crops taking in to account technician, environmental and economic criterias and their weights. Canola crop was the best option for the biodiesel production, with a global score of 74 points because of their good score in environmental criterias, wich had a higher weight than the other criterias. Corn crop was the second positioned, presenting good results in all criterias, followed by palm crop. The final one was soy crop with 36,67 points in this analysis.